PENGARUH PARTISIPASI MASYARAKAT DAN MOTIVASI TERHADAP TINGKAT KEBERHASILAN RURAL INFRASTRUKTUR SUPPORT- PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (RIS-PNPM) MANDIRI DI DESA WARINGIN SARI PRINGSEWU - Fajar Mutia Suri (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2021)
The participation of the community towards the success rate of the program, the influence of motivation on the success rate of the program, and the influence of community participation and motivation together affect the success rate of the Rural Infrastructure Support Program - the National Program for Community Empowerment (RIS-PNPM) Mandiri.